Off-Balance Sheet Exposure – Performance Analysis And Risk Measurement Of Indian Banks - Middi, Appala Raju (Archives of Business Research, 2016)
Banking Sector has under gone enormous changes over the decades initially from ownership to government ownership and open to competition from private and foreign banks after the liberalization of the economy in 1991. Under the regulated economic system, banks used to enjoy complete protection from the government and insulated totally from external shocks. The financial sector reforms initiated by the Government brought unforeseen changes in the general functioning of the banks; as a result banks are compelled to extend their business activities which they were distancing over the years. The exposure to off banking activities to like foreign exchange contracts has led the banks to expose to greater risks but with incremental revenues in the form of other incomes. It is necessary banks to manage the risk through the exposure to various off balance sheet activities. Key words; Government ownership; Liberalisation; regulated economy; off-balance sheet activity; Open Competition; Incremental Revenues ; Risk Exposure